2005
DOI: 10.1590/s0074-02762005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Histophatology and ultrastructure of Henneguya caudalongula sp. n. infecting Prochilodus lineatus (Pisces: Prochilodontidae) cultivated in the state of São Paulo, Brazil

Abstract: Prochilodus lineatus (Valenciennes, 1836) is a detritivorous teleost popularly known as curimba or curimbatá, is widely distributed in South American rivers and attains a relatively large size, with some specimens measuring 75 cm in length and weighing 8.2 kg (Godoy 1975). It has a high reproductive capacity, rapid growth, good acceptance on the market and is one of the most consumed fish species in Brazil. Its consumption has led to increased interest in its cultivation in fish farms throughout the country.Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
12
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
5
12
0
3
Order By: Relevance
“…n. the spores were surrounded by a thin anastomosed network of microfibrils, in Henneguya theca, Henneguya adherens, Henneguya testicularis, Henneguya rhamdia and H. rondoni, the spores were surrounded by a hyaline homogenous structure and in Henneguya malabarica and Henneguya striolata, the sheath was constituted by granulo-fibrilar structures organised into a complex ramified network. This inflammatory reaction seems to be of the same type as that observed and described in other Brazilian fishes (Martins et al 1988, Adriano et al 2005). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…n. the spores were surrounded by a thin anastomosed network of microfibrils, in Henneguya theca, Henneguya adherens, Henneguya testicularis, Henneguya rhamdia and H. rondoni, the spores were surrounded by a hyaline homogenous structure and in Henneguya malabarica and Henneguya striolata, the sheath was constituted by granulo-fibrilar structures organised into a complex ramified network. This inflammatory reaction seems to be of the same type as that observed and described in other Brazilian fishes (Martins et al 1988, Adriano et al 2005). …”
Section: Discussionsupporting
confidence: 80%
“…Thirty-six species have been described from Brazilian fauna based on light microscopy micrographs and diagrammatic illustrations (Jakowska & Nigrelli 1953, Kent & Hoffman 1984, Gioia et al 1986, Martins et al 1988, Gioia & Cordeiro 1996, Martins & Souza 1997, Barassa et al 2003a, b, Eiras et al 2004a, b, 2008, 2009, Martins & Onaka 2006, Abdallah et al 2007). Recently, ultrastructural studies of developmental stages and mature spores supported the classification of some new species of the genus Henneguya (Rocha et al 1992, Azevedo & Matos 1995, Casal et al 1997, Vita et al 2003, Adriano et al 2005, Matos et al 2005.…”
mentioning
confidence: 99%
“…infection are fairly common (ADRIANO et al, 2005;FEIJÓ et al, 2008), the present study found inflammatory infiltrates in the vicinity of the cysts. Furthermore, the special Ziehl-Neelsen staining techniques (LUNA, 1968) made it possible to mark the presence of Henneguya cysts in bone tissue and spore isolates in the gill tissue structure.…”
Section: Resultssupporting
confidence: 63%
“…The gill filaments parasitized by this myxosporeans had become crooked and deformed, such that the cartilaginous parts had withered due to pressure caused by the development of plasmodium (Figure 7 and 8). Deformities in the gill filaments brought about by parasites of the genus Henneguya have often been described in the literature (ADRIANO et al, 2005;NALDONI et al, 2009;CAMPOS et al, 2011;YE et al, 2012;AZEVEDO et al, 2014). El-Mansy & Bashtar (2002) obtained findings similar to those described in the present study, through studying parasitism by Henneguya suprabranchiae.…”
Section: Resultsmentioning
confidence: 98%
“…The results of the present study provide important insights into the myxosporidean infections found in R. quelen, which may cause significant tissue damage (MARTINS et al, 1999;ADRIANO et al, 2005aADRIANO et al, , b, 2006FEIST & LONGSHAW, 2006) or even death (MARTINS et al, 1999;FEIST & LONGSHAW, 2006). A better understanding of this freshwater microparasite fauna will be essential for the prevention and control of diseases in both wild and farmed stocks.…”
Section: Discussionmentioning
confidence: 63%